Synergizing Ergo-Technology by Integrating Physical, Cognitive, and Organizational Ergonomics for Sustainable Work System Design in Industry 4.0 - Angga Yuda Sakti; Liza Dwi Eftiza Khairunniza (Jurnal Sistem Teknik Industri, 2025)
The manufacturing industry still relies heavily on manual labor to take advantage of human flexibility. As work-related injuries increase, the importance of ergonomics in engineering is becoming more recognized. However, in small and medium-scale manufacturing, the application of ergonomics has not yet received sufficient attention. The aim of this study is to review literature on the application of ergonomics in work system design, identify common approaches, analyze the impact of ergonomics, and provide recommendations for more effective implementation. A descriptive qualitative approach with a literature review of Google Scholar-indexed articles was used. The analysis concludes that ergonomics application in manufacturing is growing, with a predominant use of quantitative methods. Additionally, integrating physical, cognitive, and organizational ergonomics has positively impacted innovation and job satisfaction. Based on these findings, future research should focus on developing integrated ergonomic interventions, long-term studies, and economic analyses to improve ergonomics implementation.